2012
DOI: 10.2478/v10181-011-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of treatment of Osteochondrosis dissecans (OCD) of shoulder joint in dogs-the results of two years of experience

Abstract: Osteochondrosis is a common and clinically important joint disorder that occurs in human and many species of animals such as pigs, horses and dogs. The aim of this article is to present the results of conservative and surgical treatment of Osteochondrosis dissecans (OCD) and to compare the recovery time in relation to race, age and extent of cartilage damage.The study was performed on 36 dogs of both sexes, aged from 4 to 24 months, weighing 12-70 kg, of different breeds (predisposed and non-specific for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
7
3
Order By: Relevance
“…It is considered a multifactorial disease, with hereditary and nutritional factors playing a significant role [19][20][21]. Since excessive intakes of calcium and energy are among the main factors for the development of the disease, it often affects mammals and birds kept on farms where fast growth is stimulated [22][23][24]. Yet another important factor conducive to the disease are distortions of hormonal balance reflected in the growth rate as well as cartilage and bone maturation.…”
Section: Osteochondritis Dissecansmentioning
confidence: 99%
“…It is considered a multifactorial disease, with hereditary and nutritional factors playing a significant role [19][20][21]. Since excessive intakes of calcium and energy are among the main factors for the development of the disease, it often affects mammals and birds kept on farms where fast growth is stimulated [22][23][24]. Yet another important factor conducive to the disease are distortions of hormonal balance reflected in the growth rate as well as cartilage and bone maturation.…”
Section: Osteochondritis Dissecansmentioning
confidence: 99%
“…The long-term clinical outcome of shoulder OCD surgery is likely related to many other factors including the location, diameter and depth of the lesion and the presence and severity of concurrent osteoarthritis. 2,4,6,8,10,22 Our surgical approach can be considered a moderately challenging, minimally invasive, efficient and inexpensive alternative to other surgical approaches including arthroscopy for treatment of OCD of the humeral head. The surgical instrumentation required is commonly available and inexpensive in relation to arthroscopic equipment.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is important, as it demonstrates the ability of radiography to detect only the more severe subclinical OC lesions in pigs reliably. Although radiography is considered currently as the standard imaging method to diagnose clinical OC [ 22 ], and most studies have investigated OC in other species [ 7 , 21 23 ], not many have focused on pigs [ 24 , 25 ]. Other studies have also shown significant correlations between both methods, which were joint dependent [ 13 , 26 ], however these studies were performed on older pigs and foals.…”
Section: Discussionmentioning
confidence: 99%